"I don't wanna be mad and sad": Using individual systemic therapy to help manage anger and low mood in an adult with a learning disability. (24th November 2020) - Birdsey, Nicola
Accessible summary: People with learning disabilities may find it useful to speak to a therapist if they struggle with difficulties like anger and low mood. Instead of seeing problems as being within the individual, some therapists think about how other people and wider relationships impact on a person's well‐being. This is called "systemic therapy" as it thinks about the wider systems (like family, work and social care teams) and how they can make difficulties better or worse. There is limited research that looks at systemic therapy with people with learning disabilities, which is surprising because individuals may have many different relationships with friends, relatives and people in different services. Some of the techniques that help things to change include the following: the therapist being curious, asking specific questions to help the individual think about their situation and working with the individual to find a different way of looking at problems. Abstract: People with learning disabilities have historically been overlooked in research investigating the efficacy of therapeutic interventions, despite the increased prevalence of mental health difficulties among this population. As it is not uncommon for individuals with learning disabilities to be part of different relational systems (including access to a range of services), it seems logical to consider wider systems when seeking to understand difficulties that individuals may experience. While it is encouraging that there is growing interest in the use of systemic interventions for people with learning disabilities, there is limited peer‐reviewed research exploring psychological difficulties from a systemic lens. This paper seeks to address the gap in literature by presenting a case where individual systemic therapy is used to help an adult with a learning disability to manage low mood and anger. The paper documents the therapist's clinical decision‐making and learning from this case, with the hope that it encourages others to consider systemic interventions for people with learning disabilities in future.